Gilman Salakhov’s Role and Importance in Azerbaijani Music Culture - Agaverdi, Nigar Bayramova (Cultural and religious studies, 2020)
Azerbaijani music has been created and polished by the people for centuries, and reflects the people’s spiritual strength, desire for freedom, ideas, and hopes. Azerbaijani music has been passed down from generation to generation, lived in oral traditions, and has always been distinguished by its antiquity and rich culture. Many concepts have emerged in the musical-aesthetic-concepts of antiquity and the Middle Ages, and categories of aesthetic analysis of music have been formed. Music and musical aesthetics have historically been widespread, and have shaped various socio-cultural forms in a forward-looking way. The rich musical heritage created in different periods since ancient times are undoubtedly a proof of the genetic talent inherent in every generation of the Azerbaijani people. Our national musical instruments, adapted to the emotional color, rhythm, tempo and art of Azerbaijani folk music, have passed a long historical development and brought many aspects of traditional music performance and creativity to the present day. They are one of the elements that connect the future of our musical culture with the past. Traditional music and musical instruments, which are still played today, reflect the main features of Azerbaijan’s national musical thinking and artistic creativity. Information on komuz and kilkomuz, the ancestors of stringed and plectrum musical instruments in the origin and development of Azerbaijani folk musical instruments, is also found in examples of oral folk art, in the all-Turkic monument "Kitabi-Dada Gorgud". According to written sources, 88 musical instruments, including 32 string and 23 wind instruments, were widely used in Azerbaijani performing arts. Information about this is found in the chronicles of ancient historians, in the works of medieval thinkers Safiaddin Urmavi, Abdulgadir Maragayi, Dervish Ali Changi, Qatran Tabrizi, and others on musicology.